RELATIONS ACADEMIC QUALIFICATIONS AND PROFESSIONAL ATTITUDE MASTER CLASS ON THE PERFORMANCE LEARNING SDN - Andi Asmara (Universitas Negeri Makassar, 2016)
This research was that aimed: 1) to know teachers academic qualification that basically from elementary education field and non elementary education field, 2) to know teachers professional attitude that basically from elementary education field and non elementary education field, 3) to know teachers learning performance that basically from elementary education field and non elementary education field 4) to find out the correlation of teacher academic qualification and learning performance that basically from elementary education field, 5) to find out the correlation of teacher academic qualification and learning performance that basically from non elementary education field, 6) to find out the correlation of teacher professional attitude and learning performance that basically from elementary education field, 7) to find out the correlation of teacher professional attitude and learning performance that basically from non elementary education field and 8) to find out the correlation of academic qualification and professional attitude to learning performance. The method used was ex post facto with correlational form. The population in the study are 28 elementary school teacher spread in 14 villages at Ajangale District Bone Regency. Researcher use population as sample in the study. Data were analyzed by descriptive and inferensial. The data obtained from samples were analyzed by simple and multiple correlation. The result shows: 1) Teacher academic qualification are basically from non elementary education field, 2) teacher professional attitude from elementary education field are higher than non elementary education field, 3) teacher learning performance from elementary education field are higher than non elementary education field, 4) there is a positive and significant correlation of academic qualification and learning performance that basically from elementary education field, 5) there is a positive and significant correlation of academic qualification and learning performance that basically from non elementary education field, 6) there is a positive and significant correlation of professional attitude and learning performance that basically from elementary education field, 7) there is a positive and significant correlation of professional attitude and learning performance that basically from non elementary education field, and 8) there is a positive and significant correlation of academic qualification and professional attitude all together to learning performance.